Astrophysics is Easy! : An Introduction for the Amateur Astronomer - Inglis, Mike ((Patrick Moore's Practical Astronomy Series))
Contenido: 1) Herramientas de la profesión; 2) El medio interestelar; 3) Estrellas; 4) Galaxias. Apéndices.